Pentingnya pengembangan bahan ajar bahasa Inggris berbasis multimedia - Imam Mudofir (Jurnal Linguistik Terapan, 2016)
The need of mastery English as international language is felt in any fields of life. Therefore, it is considered by Indonesia government by making a decision that English is one of the foreign language subjects is taught in the schools. The problem is English instruction in Indonesia is not successful yet. One of the reasons is caused by lacking of English material based on multimedia in English teaching process. It is needed an English material development in the field of instructional technology which has a purpose of teaching and learning process will be effective and appeal which gives a high motivation for the students to study English. The development of English material by following steps namely define the types instructional multimedia, define the theme of material, arrange the storyboard, use the analyse, imitate, and modification technique, and memorize three receipts of success story. Therefore, there is an integration between the development of English material and multimedia.